2018
DOI: 10.1186/s12967-018-1591-7
|View full text |Cite
|
Sign up to set email alerts
|

Intra-articular injection of two different doses of autologous bone marrow mesenchymal stem cells versus hyaluronic acid in the treatment of knee osteoarthritis: long-term follow up of a multicenter randomized controlled clinical trial (phase I/II)

Abstract: BackgroundMesenchymal stromal cells (MSCs) are a promising option to treat knee osteoarthritis (OA). Their safety and usefulness have been reported in several short-term clinical trials but less information is available on the long-term effects of MSC in patients with osteoarthritis. We have evaluated patients included in our previous randomized clinical trial (CMM-ART, NCT02123368) to determine their long-term clinical effect.MaterialsA phase I/II multicenter randomized clinical trial with active control was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
90
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 6 publications
5
90
0
2
Order By: Relevance
“…The use of co-adjuvants with BM-MSCs in the treatment of OA is a topic of interest. Some authors report functional and clinical improvement without the use of coadjuvants, and others report clinical improvement with the use of HA as an adjuvant for BM-MSCs, while the use of PRP as adjuvant is still controversial [28,33,34]. The clinical results published without co-adjuvants seems to be comparable with our results using BM-MSC and PRGF ® .…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The use of co-adjuvants with BM-MSCs in the treatment of OA is a topic of interest. Some authors report functional and clinical improvement without the use of coadjuvants, and others report clinical improvement with the use of HA as an adjuvant for BM-MSCs, while the use of PRP as adjuvant is still controversial [28,33,34]. The clinical results published without co-adjuvants seems to be comparable with our results using BM-MSC and PRGF ® .…”
Section: Discussionsupporting
confidence: 82%
“…We present the results of a phase II clinical trial that followed a previous phase I clinical trial focused primarily on safety and feasibility, with promising secondary e cacy results using a dose of autologous 100 million BM-MSCs, and with a clinical improvement that remained in long-term follow-up [18,33].…”
Section: Discussionmentioning
confidence: 99%
“…The use of co-adjuvants with BM-MSCs in the treatment of OA is a topic of interest. Some authors report functional and clinical improvement without the use of coadjuvants, and others report clinical improvement with the use of HA as an adjuvant for BM-MSCs, while the use of PRP as adjuvant is still controversial [28,33,34].…”
Section: Discussionmentioning
confidence: 99%
“…It has been recently shown that single intra‐articular injection of in vitro expanded autologous bone marrow MSC is a safe and feasible method that results in long‐term clinical and functional improvement of knee OA . To avoid the long and costly culture period, we proposed a one‐step in situ repair approach using a potential trigger for recruitment of endogenous MSC into the OA side and thereby enhance regeneration. The results of this and other studies suggest that the chemokine CCL25 affects the migration of MSC.…”
Section: Discussionmentioning
confidence: 99%